Stages and demands in the careers of Canadian National Hockey League players - Battochio, R. C.; Stambulova, N.; Schinke, R. J. (Journal of Sports Sciences, 2016)
Researchers have identified some demands of Canadian National Hockey League (NHL) players, yet there is little direction for players hoping to reach the lucrative league. The objectives of this study were to identify the stages, statuses and demands in Canadian NHL players` careers and propose an empirical career model of Canadian NHL players. In total, 5 rookies, 5 veterans and 13 retirees had their interviews undergo an interpretive thematic analysis. Prospects face the NHL combine, training camp and minor league assignment. While developing into NHL players, rookies deal with NHL call-ups, team competition and formative production while sophomores seemed preoccupied by the opposition. Prime veterans become All-Stars by garnering point production and challenging for the Stanley Cup while seasoned veterans remain relevant through training camps. A discussion about the model`s viability is followed by applications for sport psychology researchers and practitioners.